2013
DOI: 10.1530/rep-12-0330
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of temperature on reactive oxygen/nitrogen species production in rat pachytene spermatocytes and round spermatids

Abstract: Reactive oxygen species (ROS) and reactive nitrogen species (RNS) like superoxide and nitric oxide are produced by testis and spermatogenic cells in response to heat stress. However, the magnitude and mechanisms of this production in spermatogenic cells have not been described. In this work, we evaluated ROS/RNS production, its pharmacology, mitochondrial oxidative metabolism, membrane potential and antioxidant capacity at different temperatures in isolated rat pachytene spermatocytes and round spermatids. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The ROS and their derived reactive nitrogen species have been characterized as the main contributors to cell death in hyperthermia (43). In this study, we correlated the cold response to an increase in both [ROS] and apoptosis of spermatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS and their derived reactive nitrogen species have been characterized as the main contributors to cell death in hyperthermia (43). In this study, we correlated the cold response to an increase in both [ROS] and apoptosis of spermatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For normal spermatogenesis, generation of ROS during heat stress and involvement in spermatogenic cell damage are common [35][36][37]. In this context, it is not surprising to see the up-regulation of YES1 expression and activity in PS, as these cells are more susceptible to oxidative stress at high temperatures (408C) [38].…”
Section: Discussionmentioning
confidence: 99%
“… 14 15 Experimental models have also shown that transient mild testicular hyperthermia can destroy the balance between oxidative capacity and antioxidant capacity. 16 17 The human spermatozoa are highly susceptible to oxidative stress, high levels of free radicals, and reactive oxygen species (ROS), including the superoxide anion and hydrogen peroxide (H 2 O 2 ). 18 19 Oxidative stress can be deleterious and cause oxidative damage to the sperm plasma membrane and DNA fragmentation of both the nuclear and mitochondrial genomes.…”
Section: Introductionmentioning
confidence: 99%